Antropologia Maurice’a Blondela i kryzys modernistyczny - Zieliński, Sławomir (Śląskie Studia Historyczno-Teologiczne, 2011)
The paper presents an outline of the modernistic crisis, it concentrates especially on its French specific character, refers to many main representatives and reaction of Magisterium Ecclesiae. The first period of academic creativity of the French philosopher Maurice Blondel falls on that difficult period of modernistic crisis, what left clear traces especially on his anthropological thoughts. There are numerous references to that epoch in philosopher’s works. He expressed care about providing both an autonomy for rational philosophical argumentation, as well as an autonomy for the transcendence of the supernatural order. He devoted himself totally to profound criticism of the new culture and analysis of immanent limits of its positive nature. After presentation of basic papers of the French philosopher from that period, several, most important ideas, which were created because of the influence of modernism, such as: immanent method, criticism of historicism and extrinsicism, and Christological theme, have been outlined. Blondel marked main lines of his anthropology emphasizing clearly his distance to modernism by fighting representatives of radical rationalism and criticizing scholastic method.